International experiences in multicriteria decision analysis (MCDA) for evaluating orphan drugs: a scoping review. (4th July 2019) - Lasalvia, P; Prieto-Pinto, L; Moreno, M; Castrillón, J; Romano, G; Garzón-Orjuela, N; Rosselli, D
ABSTRACT: Introduction : Orphan diseases are low-prevalence conditions with chronically debilitating or life-threatening consequences. Their treatments are generally called orphan drugs (OD). Health–technology assessment processes have traditionally considered cost-effectiveness analysis (CEA), when making reimbursement and pricing decisions for health-care plans. Valuing OD with standard CEA raises important issues due to uncertain evidence, inability to meet cost-effectiveness thresholds for reimbursement and high budget impact, among others. Multi-criteria decision analysis (MCDA) allows to overcome these issues and improve the technical and ethical quality of decisions regarding prioritization, coverage, and reimbursement of OD. Areas covered : A scoping review was conducted in order to characterize MCDA frameworks for assessing OD and implementation experiences. We reviewed electronic databases (Medline, Embase, Cochrane Library, EBSCO, CINAHL, EconLit, Web of Science, LILACS, Google Scholar) key journals (Orphanet Journal of Rare Diseases and Value in Health) and organization repositories. Expert opinion : The theoretical framework for MCDA considers areas related to characteristics of orphan diseases and their technologies' clinical and economic impact. Participation processes are critical in incorporating societal values in weighting different dimensions and constructing decision rules. Local implementation pilots considering different stakeholders are necessary in order to pinpoint specific barriers and opportunities.